Co-culture of monocytes and zona fasciculata adrenal cells: An in vitro model to study the immune-adrenal cross-talk. (15th April 2021) - Fudulu, Daniel P.; Horn, George; Hazell, Georgina; Lefrançois-Martinez, Anne-Marie; Martinez, Antoine; Angelini, Gianni D.; Lightman, Stafford L.; Spiga, Francesca
Abstract: The hypothalamic-pituitary-adrenal axis is the primary neuroendocrine system activated to re-establish homeostasis during periods of stress, including critical illness and major surgery. During critical illness, evidence suggests that locally induced inflammation of the adrenal gland could facilitate immune-adrenal cross-talk and, in turn, modulate cortisol secretion. It has been hypothesized that immune cells are necessary to mediate the effect of inflammatory stimuli on the steroidogenic pathway that has been observed in vivo . To test this hypothesis, we developed and characterized a trans-well co-culture model of THP1 (human monocytic cell)-derived macrophages and ATC7 murine zona fasciculata adrenocortical cells. We found that co-culture of ATC7 and THP1 cells results in a significant increase in the basal levels of IL-6 mRNA in ATC7 cells, and this effect was potentiated by treatment with LPS. Addition of LPS to co-cultures of ATC7 and THP1 significantly decreased the expression of key adrenal steroidogenic enzymes (including StAR and DAX-1), and this was also found in ATC7 cells treated with pro-inflammatory cytokines. Moreover, 24-h treatment with the synthetic glucocorticoid dexamethasone prevented the effects of LPS stimulation on IL-6, StAR and DAX-1 mRNA in ATC7 cells co-cultured with THP1 cells. Our data suggest that the expression of IL-6 and steroidogenic genes in response to LPS depends on the activation of intra-adrenal immune cells. Moreover, we also show that the effects of LPS can be modulated by glucocorticoids in a time- and dose-dependent manner with potential implications for clinical practice. Highlights: We propose a co-culture model of adrenocortical cells and monocytes to investigate the immune-steroidogenic cross-talk. LPS stimulation of co-cultured ATC7-THP1 cells increases IL-6 mRNA and reduces StAR and DAX-1 mRNA expression. Cytokines effects on IL-6 and steroidogenic genes mRNA are different in co-cultured ATC7- THP1 cells and ATC7 cells alone. DEX prevents the LPS induced IL-6 mRNA expression and steroidogenic gene in ATC7-THP1 cells in a dose-dependent manner. ACTH induced adrenal IL-6 mRNA expression and steroidogenic genes activation are modulated by co-culture with THP1 cells.